Analysis of Tourist Loyalty and Satisfaction Based on Destination Image of Sustainable Tourism in West Java - Siti Zakiah; Edwin Baharta; Deni Hermana (Jurnal Ilmu Manajemen Advantage, 2023)
Sustainable tourism is not only an actualization of the resort hotel's understanding of the wishes of tourists who have attitudes and behavior oriented toward sustainability. Sustainable tourism is a form of responsibility towards the world. This research aims to analyze Loyalty and Tourist Satisfaction changes based on the Destination Image of Sustainable Tourism in West Java. The research approach uses a casual study with a randomly selected sample of 240 in sustainable tourism locations in West Java both online and offline. The results of the study show that tourists feel and realize positive impressions that are known through travel experiences affect satisfaction and loyalty. Tourist groups who have personal value preferences on sustainability have a loyal attitude towards service providers and are willing to advocate for efforts to ensure sustainability if possible facilitated by the provider. Destination image affects the level of loyalty either directly or through satisfaction. The theoretical implication is the importance of customer value preferences as a basis for the development of sustainable tourist destinations. The practical implication is that providers must understand tourist imagery processing as a complex process determining loyalty to sustainability.